(3agQS eQBI GdLfGfs - (3GdjGaYj , Yaja GdOjf YHO Gddg Hf CSYO Hf Ydj GdjGaYj Gdjefj, Yaja GdOjf,J (B768 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEfg deG cGf JGQjN SjOi CHh eMeO YHO Gddg Hf GSYO GdjGaYi ai eYQaI MhGOK GdReGf hJbdH CMhGd GdEfSGf MQa GdgeRI EHQGgje Hf QShd Gdgd Udi Gdgd Ydjg hSde Jhai hgh GHf SfI s
(3BNQgG (B:s
(3GdMSf Hf Ydi Hf CHj WGdH QVi Gddg YfgeG hHg JeGe GdKdKjf ef GdSfjf Je Pdc hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B72 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B34s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs